Photorhabdus antumapuensis sp. nov., a novel symbiotic bacterial species associated with Heterorhabditis atacamensis entomopathogenic nematodes. Issue 10 (10th October 2022) - Castaneda-Alvarez, Carlos; Machado, Ricardo A. R.; Morales-Montero, Patricia; Boss, Anja; Muller, Arthur; Prodan, Simona; Zamorano, Alan; San-Blas, Ernesto; Půža, Vladimír; Aballay, Erwin
Abstract : One motile, Gram-negative, non-spore-forming and rod-shaped symbiotic bacterium, strain UCH-936 T, was isolated from Heterorhabditis atacamensis nematodes. Results of biochemical, physiological, molecular and genomic analyses suggest that it represents a new species, which we propose to name Photorhabdus antumapuensis sp. nov. Digital DNA–DNA hybridization shows that strain UCH-936 T is more closely related to Photorhabdus kleinii DSM 23513 T, but shares solely 50.5 % similarity, which is below the 70% cut-off value that delimits species boundaries in bacteria. Phylogenetic reconstructions using whole-genome sequences show that strain UCH-936 T forms a unique clade, suggesting its novel and distinct taxonomic status again. Similarly, comparative genomic analyses shows that the virulence factor flagella-related gene fleR, the type IV pili-related gene pilL and the vibriobactin-related gene vibE are present in the genome of strain UCH-936 T but absent in the genomes of its closest relatives. Biochemically and physiologically, UCH-936 T differs also from all closely related Photorhabdus species. Therefore, Photorhabdus antumapuensis sp. nov. is proposed as a new species with the type strain UCH-936 T (CCCT 21.06 T =CCM 9188 T =CCOS 1991 T ).